The Influence of Financial Distress, Capital Intensity, and Leverage on Tax Avoidance with Institutional Ownership as Moderating Variable in Food and Beverage Companies at IDX - Diah Juliawati; Ali Sandy Mulya (Journal Research of Social Science, Economics, and Management, 2025)
The research is motivated by persistent tax revenue shortfalls and reported losses due to tax avoidance practices, particularly within Indonesia's strategic food and beverage sector. This research aims to analyze and empirically test the influence of financial distress, capital intensity, and leverage on tax avoidance in food and beverage sub-sector companies on the Indonesia Stock Exchange (BEI) from 2020–2024. This quantitative research uses the Moderated Regression Analysis (MRA) method, processed with Eviews 13. The population for this study comprises food and beverage sub-sector companies, with a sample size of 31 companies. Based on the research results, it was found that financial distress has a positive effect on tax avoidance, while capital intensity and leverage do not affect tax avoidance. The moderation test results indicate that the institutional ownership variable cannot moderate the influence of financial distress, capital intensity, and leverage on tax avoidance. The study concludes that these specific financial factors are not primary drivers of tax avoidance in the sampled context, suggesting that regulators and corporate governance mechanisms should look beyond these variables to more effectively address tax compliance.